Guinea : The Economic Benefits of a Gender Inclusive Society - World Bank (World Bank, Washington, DC, 2019)
This report examines the extent of gender gaps, their economic impact, and proposes policies to improve gender equality in Guinea. Although the government of Guinea has taken actions to boost gender equality, significant challenges persist. Child marriage is widespread among girls, reducing girls’ education and resulting in among the highest rates of early childbearing worldwide. Moreover, female genital mutilation is almost universal with high societal costs on women’s health. Girls reaching adulthood have lower education levels than men, lower wages,and lower agricultural productivity. Reducing gender inequality in Guinea could potentially accelerate per capita GDP growth by up to 0.6 percentage points per year or 10.2 percent overall by 2035, according to the results of estimations from a Computable General Equilibrium Model. This is a rate of return to investment of 8.2 percent per year. Policy recommendations to tackle the gender divide focus on legislative changes and programs intended to boost the productivity of adult women, reduce the prevalence of child marriage, early child bearing, and female genital mutilation/excision.